1981
DOI: 10.1029/gl008i010p01103
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dependence of large‐scale Birkeland currents

Abstract: The seasonal dependence of large‐scale Birkeland currents has been determined from the analysis of vector magnetic field data acquired by the TRIAD satellite in the northern hemisphere. Statistical characteristics of single sheet (i.e., net currents) and double sheet Birkeland currents were determined from 555 TRIAD passes during the summer, and 408 passes during the winter (more complicated multiple‐sheet current systems were not included in this study). The average Kp value for the summer events is 1.9 and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
118
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 17 publications
35
118
1
Order By: Relevance
“…For the events between 8 -11 MLT, the mean current for sunlit (dark) events was 8.6 (6.0); for 13-16 MLT sector, the mean was 7.7 (5). This dependence has been used by previous studies, including Fujii et al [1981], as evidence that the currents are due to a voltage source. Other studies have also addressed the question of whether the magnetosphere acts as a constant current source or a voltage source.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the events between 8 -11 MLT, the mean current for sunlit (dark) events was 8.6 (6.0); for 13-16 MLT sector, the mean was 7.7 (5). This dependence has been used by previous studies, including Fujii et al [1981], as evidence that the currents are due to a voltage source. Other studies have also addressed the question of whether the magnetosphere acts as a constant current source or a voltage source.…”
Section: Discussionmentioning
confidence: 96%
“…They found good correlation with IMF B z for B z < 0 and with similar parameters, consistent with reconnection as the current source. Their data set was separated by the sign of IMF B y because previous studies showed changes in the region of maximum current with this parameter [Potemra et al, 1979] and restricted to summer because Fujii et al [1981] showed changes in the size of current with season.…”
Section: Introductionmentioning
confidence: 99%
“…6 background ionospheric conductivity due to solar radiation is higher in the former. However, the dependence on the ionospheric conductivity may be di erent between the voltage generator and the current one, as discussed for the quiet time geomagnetic variations by Fujii et al (1981) and Fujii and Iijima (1987). The northsouth asymmetry is not basically expected for the current generator, such as discussed by Vickrey et al (1986) for Birkeland currents of intermediate scale size.…”
Section: Asymmetry Of Ionospheric Current System In Solsticementioning
confidence: 92%
“…During the summer and winter seasons, or more specifically, when the magnitude of the dipole tilt angle is appreciable, Birkeland currents become asymmetric about the low-latitude boundary layer. In the summer hemisphere this current is stronger mainly because the conductivity of the polar ionosphere is higher [Fujii et al, 1981]. Because of this Birkeland current asymmetry, a net magnetic flux, westward on the dawn side and eastward on the dusk side of the inner magnetosphere, is enclosed by geomagnetic field lines.…”
mentioning
confidence: 99%